The Comparative Analysis on the Consumption Behavior of Students of Brawijaya University in Food Purchasing in Food Stalls and Cafe in Malang - Fitriandini, Isna Ayu Putri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Fast Food becomes one of the alternatives of busy urban society regardless the age as they have been overwhelmed with so many activities so that they do not have time to cook by themselves either at home or at the dorm. All of these are made possible since nowadays there are so many available facilities eating places such as cafe or food stalls. The existence of cafe and food stall currently fulfills the needs of those who want something more instant, easy and complete. This phenomenon is far different from what happened ten years ago when daily meals are more likely to be done at home presented by a housewife or those living in a boarding house will have their own cooking. This research uses descriptive quantitative method to do the appropriate research in investigation a condition in two ways: interview and questionnaire. This method enables the researcher to describe in more a detail the level of consumption of Brawijaya University students in purchasing food from food stalls and cafes in Malang. At the end, the results obtained in this study are expected to be able to describe the the degree of difference of those consumers who choose to buy food either at the food stall or cafe. Consumers habit of eating food at cafes will later give negative impact for food stalls business owners. Keywords: consumption behavior, food stall, cafe, and lifestyle.